CHROMOSOME STUDY ON THE SUBMERGED MOSS COLLECTED FROM ANTARCTIC LAKES (14th Symposium on Polar Biology) - カンダ, ヒロシ; オカダ, ヒロシ; KANDA, Hiroshi; OKADA, Hiroshi (National Institute of Polar Research, 1993)
P(論文) The submerged moss, which was found on lake beds in the Syowa Station area, East Antarctica was studied karyologically and taxonomically. The chromosome number of the moss showed to have n=23 and is expressed as n=22+m because it has a smallest chromosome with negative heteropycnosis. It may be appropriate to assign this moss to Leptobryum pyriforme (HEDW.) WILS. judging from the chromosome number in addition to some morphological features such as sexuality and tubers. departmental bulletin paper